Construction of multifunctional coating with cationic amino acid-coupled peptides for osseointegration of implants - Bingyang Zhao; Yilong Dong; Xinkun Shen; Wei He; Hairu Jin; Lili yao; Sheng wu Zheng; Xingjie Zan; Jiming Liu (Materials Today Bio, 2023)
Osseointegration is an important indicator of implant success. This process can be improved by coating modified bioactive molecules with multiple functions on the surface of implants. Herein, a simple multifunctional coating that could effectively improve osseointegration was prepared through layer-by-layer self-assembly of cationic amino acids and tannic acid (TA), a negatively charged molecule. Osteogenic growth peptide (OGP) and the arginine-glycine-aspartic acid (RGD) functional polypeptides were coupled with Lys6 (K6), the two polypeptides then self-assembled with TA layer by layer to form a composite film, (TA-OGP@RGD)n. The surface morphology and biomechanical properties of the coating were analyzed in gas and liquid phases, and the deposition process and kinetics of the two peptides onto TA were monitored using a quartz crystal microbalance. In addition, the feeding consistency and adsorption ratios of the two peptides were explored by using fluorescence visualization and quantification. The (TA-OGP@RGD)n composite membrane mediated the early migration and adhesion of cells and significantly promoted osteogenic differentiation and mineralization of the extracellular matrix in vitro. Additionally, the bifunctional peptide exhibited excellent osteogenesis and osseointegration owing to the synergistic effect of the OGP and RGD peptides in vivo. Simultaneously, the (TA-OGP@RGD)n membrane regulated the balance of reactive oxygen species in the cell growth environment, thereby influencing the complex biological process of osseointegration. Thus, the results of this study provide a novel perspective for constructing multifunctional coatings for implants and has considerable application potential in orthopedics and dentistry.